Fueling the future: A techno-economic evaluation of e-ammonia production for marine applications - Nesrine Souissi (The Oxford Institute for Energy Studies, 2024)
This paper examines the viability of green ammonia (NH3) as a marine fuel in the transition to decarbonized shipping. While there is no singular solution for achieving decarbonization, there is increasing recognition on the pivotal role of green ammonia in decarbonizing the shipping sector. The research employs a comprehensive model to estimate production, storage, and distribution costs for 2030 and 2050, focusing on regions with competitive photovoltaic and wind power generation. Key findings indicate that while the Levelized Cost of Electricity (LCOE) is a crucial factor, the high costs associated with green ammonia are likely to persist, even with anticipated cost reductions by 2030. Factors such as technological innovations and economies of scale may contribute to cost declines, yet significant reductions are contingent on supportive government policies. By 2050, costs are expected to remain elevated, emphasizing the necessity of policy support for economic feasibility. Ultimately, enhancing the economic viability of green ammonia requires a multifaceted approach, including financial incentives, regulatory frameworks, and technological advancements. The paper underscores that a diverse array of alternative fuels, including green ammonia, is essential to meet the energy demands of the maritime industry, advocating for a flexible, multi-fuel strategy to address the challenges of decarbonization of the shipping sector.
Keywords: 330; ammonia; Biofuels; FuelEU; Hydrogen; IEA; IRENA; methanol; policy; Renewable; Shipping; Sustainability